Inclusion without Solidarity: Education, Economic Security, and Attitudes toward Redistribution. (February 2022) - Gelepithis, Margarita; Giani, Marco
Highly educated individuals tend to be less supportive of redistribution by most accounts because they have more to lose and less to gain from it. In this article, we use European Social Survey data to develop the argument that university education reduces support for redistribution in large part independently of the improved material circumstances with which it is associated. While university encourages a range of progressive ideas related to cultural inclusivity, it simultaneously encourages conservative redistribution preferences that are reinforced—but only partly explained—by the economic security it tends to provide. In short, European universities foster norms of cultural inclusion, while simultaneously eroding norms of economic solidarity.